2021
DOI: 10.1111/iej.13660
|View full text |Cite
|
Sign up to set email alerts
|

A critical analysis of research methods and experimental models to study dentinal microcracks

Abstract: The purpose of this narrative review was to discuss the scientific milestones that led to the current understanding of the root dentinal microcrack phenomenon based on the interplay between the usage of micro-computed tomography (micro-CT) as an analytical tool alongside a close-to-mouth experimental model. In 2009, reports on the development of dentinal microcracks in extracted teeth after root canal preparation triggered an awareness of the potential for vertical root fractures (VRFs) of endodontically treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 150 publications
0
29
0
Order By: Relevance
“…According to a recent narrative review, however, endodontic shaping may not be the cause of microcrack formation. In fact, these defects can be observed in extracted and stored teeth and may be due to procedural errors in the preparation of the experimental samples, rather than merely being due to the shaping [ 54 ]. Moreover, the studies that analyze microcrack formation showed discordant results, even when compared to each other [ 28 , 34 , 39 , 40 , 41 , 42 , 44 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent narrative review, however, endodontic shaping may not be the cause of microcrack formation. In fact, these defects can be observed in extracted and stored teeth and may be due to procedural errors in the preparation of the experimental samples, rather than merely being due to the shaping [ 54 ]. Moreover, the studies that analyze microcrack formation showed discordant results, even when compared to each other [ 28 , 34 , 39 , 40 , 41 , 42 , 44 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the results of the studies included in this revision are, therefore, attributable to many factors and are not related to the taper of the instrumentation used, but instead are probably related to: The difference in the preparation motion [ 48 , 55 , 56 ]; The cross-sectional profile and blade design [ 10 , 63 , 64 ]; The type of alloy of the instrument used [ 54 , 64 , 65 , 66 ]. …”
Section: Discussionmentioning
confidence: 99%
“…The present in vitro study was performed on human teeth extracted for periodontal reasons. Some teeth presented cracks prior to the root-end preparation, which could have been present prior to extraction or may have occurred during the extraction maneuvers or during the shaping procedures [18,24]. In fact, in vitro preparation may cause cracks more often than in vivo because of the shock-absorbing capacity of the periodontal ligament and because of the dehydration occurring during the shaping procedure [7,25].…”
Section: Discussionmentioning
confidence: 99%
“…Great interest was placed on the dentinal microcrack phenomenon by clinicians, academics and researchers over the following years. In a recent narrative review conducted on crack formation, Versiani et al analyzed how the root dentinal microcracks observed in cross-sectional images of extracted teeth are not caused by canal-shaping procedures, and dehydration often causes cracking of the dentinal tissue, regardless of canal instrumentation [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of ex vivo studies, as discussed previously, have been questioned, due to the presence of pre‐existing cracks in the sample selection (Arias & Peters, 2022; De‐Deus et al, 2014). The results of cadaver studies do not show any causal relationship between root canal shaping and the development of dentinal microcracks (Arias et al, 2014; Bahrami et al, 2017), and these results should be considered as more relevant due to absence of pre‐existing cracks (Versiani et al, 2021).…”
Section: Contributory Risk Factorsmentioning
confidence: 99%